2021
DOI: 10.2174/1574888x16999201124153753
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor and Insulin-like Growth Factor-1 based Cellular Therapies for Oxidative Stress Injury

Abstract: : Imbalance between free radicals and antioxidants causes oxidative stress by the accumulation of reactive oxygen species (ROS) in the tissues and organs. Oxidative stress occurs in many damage conditions, and the increase of ROS and reduction of antioxidants enhances inflammation, apoptosis, fibrosis and may worsen the pathology leading to organ failure. The potential therapies aim to increase antioxidants and decrease ROS. Mesenchymal stem cells (MSCs) isolated from the stroma of various tissues are multipot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, senescence is not simply the result of the increasing age, but also the result of the innate reaction under pathological conditions, such as chronic injury [ 28 ]. In recent decades, IGF1 has become a research focus, not only because inactivating the IGF1 signaling pathway can prolong life, but also because activating this signaling pathway would release inflammatory factors, aggravate the oxidative stress response and other pathological conditions, and jointly accelerate cell senescence [ 29 ]. However, it is not clear whether IGF1 is an important cause of AEC senescence in IPF.…”
Section: Discussionmentioning
confidence: 99%
“…However, senescence is not simply the result of the increasing age, but also the result of the innate reaction under pathological conditions, such as chronic injury [ 28 ]. In recent decades, IGF1 has become a research focus, not only because inactivating the IGF1 signaling pathway can prolong life, but also because activating this signaling pathway would release inflammatory factors, aggravate the oxidative stress response and other pathological conditions, and jointly accelerate cell senescence [ 29 ]. However, it is not clear whether IGF1 is an important cause of AEC senescence in IPF.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that there is need for adjustment of the application. Since it is possible to produce IGF-1 overexpressing stem cells [93], their circadian release may be one option to further investigate. Drug delivery via ROS-responsible nanoparticles represents another promising option [94].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, SOD-MSCs can reduce the inflammation in the skin through the JAK-STAT pathway ( 54 ). In psoriasis, another research found that subcutaneous administration of SOD-MSCs (UC-MSCs) in mice (2 × 10 6 cells) can ameliorate the symptoms of skin lesion by regulating the inflammatory pathways including toll-like receptor-7, nuclear factor-kappa B(NFκB), p38 mitogen-activated kinase (MAPK), and JAK-STAT pathways ( 71 ) ( Figure 2 ). Other studies indicate that hepatocyte growth factor-transduced MSCs (HGF-MSCs) also exert a better capability of antioxidant response in various acute/chronic disease ( 58 ).…”
Section: The Therapeutic Effects Of Preconditioning Mscs On Ad and Ps...mentioning
confidence: 99%